Epithets in Russian Spiritual Verses - A. A. Kotov; E. A. Mukhina (Научный диалог)
The article examines the composition and functioning of epithets in Russian spiritual verses. The relevance of the study is due to the lack of research on spiritual verses from a linguistic perspective, as well as the opportunity to explore the interaction between oral and written traditions, secular and Christian culture, which are closely intertwined in this folklore genre. A brief overview of the theory of epithet study in Russian linguistic tradition is provided, taking into account the latest research, with particular emphasis on the use of constant epithets in folklore texts of various genres. The texts of three collections of Russian spiritual verses are considered: “Collection of Russian Spiritual Verses” compiled by V. Varentsov; “The Dove Book: Russian Folk Spiritual Verses of the 11th-19th Centuries”; “Spiritual Verses of the Russian North”. Two corpora of epithets are distinguished: general folklore constant epithets and genre-specific epithets of Russian spiritual verses. Observations are made about their quantitative and qualitative composition, describing the peculiarities of their usage in relation to the genre’s specificity and explaining their correlation. A grammatical characterization of epithets is provided from the perspective of morphological expression and position within an attributive syntagm.